The Influence of Social Behavior and Business Decisions in the Digital Age: An Analysis of Economic Sociology - Alexandro Sebastian Nicholas (GoAcademica Research & Publishing, 2023)
The digital age has transformed the way we collect and analyze data on social behavior and business decisions. Big data analytics is a powerful tool that can help us uncover insights and patterns that were previously hidden, and can support more informed decision-making. This paper reviews the research methods that have been used to study social behavior and business decisions in the digital age, with a focus on big data analytics. We discuss the challenges and opportunities associated with collecting and analyzing large volumes of data, and highlight some of the key ethical considerations that researchers need to be aware of. We also provide examples of how big data analytics has been used to address important questions in the areas of social behavior and business decisions, and discuss some of the implications of these findings for theory and practice.